Framework for sustainable human resource development based on local wisdom Poda na Lima: A study of the Sipirok migrant community in Medan City - Julianto Hutasuhut; Ega Siddik; Indra Muda; Adrial Falahi; Fathin Abdullah (Priviet Social Sciences Journal, 2025)
The Society 5.0 era requires human resource development that goes beyond technical competence to include strong moral integrity and sustainability principles. Local wisdom, such as the Poda na Lima philosophy from the Sipirok community, offers potential as a foundation for holistic HR development. This study examines the relevance of Poda na Lima’s philosophy to HR development among Sipirok migrants living in Medan City. Using a descriptive qualitative approach, the study involved 12 informants from various professional backgrounds selected through purposive and snowball sampling techniques. Data collection was carried out through in-depth interviews, participatory observation, and documentation, and then analyzed using the Miles, Huberman, and Saldana data analysis model with support from the source, method, and theoretical triangulation. Results show that the five principles of Poda na Lima—Paias Rohamu (Cleansing the Soul), Paias Pamatangmu (Cleansing the Body), Paias Parabitonmu (Cleansing Clothing), Paias Bagasmu (Cleansing the House), and Paias Pakaranganmu (Cleansing the Environment)—have strategic relevance to modern HR development concepts. This philosophy works as an operational framework for building professional competence, character, and performance, while offering solutions to globalization challenges. This research confirms that Poda na Lima can be positioned as an Indigenous Management Framework that provides a competitive advantage by integrating noble local wisdom values with contemporary management principles